Resposta patológica do câncer de mama de pacientes tratadas por quimioterapia neoadjuvante e correlação com a sobrevida - Brito, Érika de Abreu Costa (2022)
Background: Neoadjuvant chemotherapy (NACT) consists of the use of chemotherapy drugs preceding the surgical treatment of the primary tumor to enable the performance of conservative surgeries. The pathological study of the post-NACT tissues revealed several changes. The relationship between changes and the response to NACT has stimulated several studies, with different parameters and results. Objectives: The main objectives of this study were to evaluate the correlation of new pathological parameters related to NACT and to correlate the classic pathological parameters with five-year overall survival (OS) and breast cancer-specific survival (CSS). Material and methods: A retrospective cohort of 142 NACT-treated female patients with primary breast cancer diagnosed between January 2011 and December 2017 was analyzed. Slides were reviewed by two independent pathologists. Treatment-related parameters were macroscopic tumor patterns, median tumor cellularity percentage and grouped, size of the largest axillary metastasis, pattern of regression in lymph nodes, and post-NACT final morphological patterns of regression. For statistical analysis, the following were used: chi-square test and Fisher test to assess the hypothesis of independence of the categorical variables Mann-Whitney test to assess the hypothesis of equality of medians between two independent groups, Kaplan-Meier method to assess the probability of sample survival and Gehan-Breslow test to test the hypothesis of no difference in the curves of survival for the different groups Results: The median 5-year survival was 53.7 months (IQI: 42.2 to 60.8 months). The median 5-year survival was 53.7 months (IQI: 42.2 to 60.8 months). The 5-year status was 105 patients alive (73.9%) and 37 deaths (26.1%) for OS. The 5-year status was 114 patients alive (80.3%) and 28 deaths (19.7%) for CSS. Pathologic complete response (absence of residual invasive disease in both breast and axillary lymph nodes) was observed in 29 (20.4%) of 142 (100%) surgical specimens. Regarding univariate analysis of parameters related to the treatment effect, macroscopic pattern of the tumor, percentage of cellularity and median of the largest lymph node metastasis presented independent prognostic values for OS and CSS. Classical parameters such as pathological staging, nuclear grade, mitotic index and lymphovascular invasion were also correlated with survival. Regarding multivariate analysis, cellularity equal to or greater than 40% had a higher chance of death for OS (HR: 6.59; 95% CI: 2.30 to 18.9; p < 0.001 HRp; 3.4; CI 95 %: 1.12 to 10.4; p = 0.031) and for CSS (HR 10.5; 95% CI: 2.45 - 44.6; p = 0.002; HRp 6.78; 95% CI: 1, 50 - 30.6; p = 0.013). The classic parameter of worst prognosis was axillary status ypN1+2+3 versus ypN0 for both OS (HR; 3.56; CI95%: 1.51, 8.38; p = 0.004; HRp: 2.65; CI95%:1.09, 6.48; p = 0.032) and CSS ( HR; 3.56; CI95%: 1.51, 8.38; p = 0.004; HRp: 2.65; CI95%:1.09, 6.48; p = 0.032) Conclusions: Our findings support the incorporation of the percentage of tumor cellularity in the anatomopathological reports of surgical specimens from patients treated with NACT and confirm the prognostic value of the classic parameters after neoadjuvant treatment.